Advances and Applications of Three-Dimensional-Printed Patient-Specific Chest Phantoms in Radiology: A Systematic Review - Silberstein, Jenna; Sun, Zhonghua (MDPI AG, 2024)
Lung cancer screening would benefit from low-dose CT protocols optimized by means of a highly accurate three-dimensional radiation-equivalent thoracic phantom. However, whether three-dimensional (3D)-printed chest phantoms have been used for this purpose is unclear, as is their current scope of application. This systematic review aims to explore the range of applications of 3D-printed thoracic phantoms, along with the techniques, materials, and anatomical structures they replicate. Relevant articles were identified using a systematic search strategy across PubMed and Scopus databases, based on pre-determined selection criteria. In total, 20 articles were eligible and critically analysed, all consisting of phantom experiments. Findings reveal that a diverse range of thoracic organs have been 3D-printed, predominantly via fused-deposition modelling incorporating polylactic acid, however, often representing discreet or limited structures. A comprehensive radiation-equivalent chest phantom that mimics the full gamut of thoracic structures is warranted. Most studies are still in their preliminary testing stages, primarily assessing the feasibility of creating morphologically accurate thoracic structures with radiation equivalence. Few studies have progressed to explore their applications. Notably, most investigations into applications have concentrated on dose reduction and CT protocol optimisation for cardiac purposes, rather than pulmonary applications, despite the inclusion of lung cancer nodules in some phantoms.